2013
DOI: 10.3748/wjg.v19.i13.2092
|View full text |Cite
|
Sign up to set email alerts
|

Missed diagnosis of early gastric cancer or high-grade intraepithelial neoplasia

Abstract: AIM: To investigate the causes of missed diagnosis of early gastric cancer (EGC) or high-grade intraepithelial neoplasia (HGIN) in Chongqing, China. METHODS: The present study summarizes 103 cases of EGC/HGIN detected by esophagogastroduodenoscopy (EGD) and pathological analysis from January 2010 to December 2011. Dimethyl silicone oil was administrated orally 15 min before the EGD procedures. The stomach was cleaned by repeated washing with saline when the gastroscope entered the stomach cavity. Suspected EGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 21 publications
1
41
0
2
Order By: Relevance
“…Studies have shown that misdiagnosis can be significantly reduced if ≥4 biopsy fragments are collected. 14 , 15 However, it is difficult to ensure that a large number of biopsy fragments is harvested from small lesions, and diagnoses can only be improved by increasing the accuracy of the biopsy or by using other means.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that misdiagnosis can be significantly reduced if ≥4 biopsy fragments are collected. 14 , 15 However, it is difficult to ensure that a large number of biopsy fragments is harvested from small lesions, and diagnoses can only be improved by increasing the accuracy of the biopsy or by using other means.…”
Section: Discussionmentioning
confidence: 99%
“…11 This result is comparable to post-colonoscopy colorectal cancer rates of 2.5-7.7% in Western populations. 12 Notably, upper gastrointestinal cancer miss rates in some studies from the Far East are higher than those reported for the West, [13][14][15][16] but these series include early gastric neoplasia, whereas the Western publications report predominantly advanced cancers (Table 1).…”
Section: Introductionmentioning
confidence: 90%
“…[52][53][54] During endoscopic examinations cancerous lesions at the gastro-oesophageal junction are more commonly missed than in other regions. 15 Emphasis should be placed on careful e xamination of these areas.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…A recent analysis of the endoscopic miss rate of 103 patients with EGC and high-grade dysplasia revealed that the miss rate of lesions in the esophagogastric junction area was statistically high ( p =0.022), while lesions in the upper gastric area were relatively more frequently missed than those in the lower gastric and antral areas. 11 It is well known that the blind spots of upper gastric endoscopy are the cardia, greater curvature of the upper part, posterior area of the body, pyloric area, and lesser curvature of the antrum ( Fig. 1 ).…”
Section: Endoscopic Examination Without Blind Spotsmentioning
confidence: 99%